The inhibition of human pathogens: Trichophyton rubrum and Trichoderma harzianum by a natural product - Hafidh, Rand Riadh; Abdulamir, Ahmed Sahib; Law, Se Vern; Abu Bakar, Fatimah (Science Publications, 2010)
Problem statement: A number of studies have recently conducted to identify novel and potent antifungal components from natural products. One of the reasons is to overcome the antifungal resistant developed against most of commercially available drugs. Studies confirmed that mung beans have increased phenolic compounds and enhanced defenses during germination. Approach: We hypothesized that antifungal activities might be found in sprouts of mung beans, or Vigna radiate (L.) R. Wilczek. The screening method was conducted using disc diffusion assay against 12 fungi. It was followed by the evaluation of the minimum inhibitory concentration and the minimum fungicidal concentration. Results: The screening results revealed a potential antifungal activity by mung bean sprout extract against 2 out of 12 fungi including remarkable antifungal activity against human fungal pathogens, Trichophyton rubrum and Trichoderma harzianum. The potential antifungal activity of mung bean sprout reflects effective quality/quantity of polyphenolic compounds present after bean germination. Conclusion/Recommendations: This unprecedented study showed that mung bean sprout extract is a potential source for novel antifungal compound (s) that is inexpensive and readily available at a large scale for pharmaceutical companies.